Festive Ukrainian cooking - Farley, Marta Pisetska (University of Pittsburgh Press, 1990)
Shares menus for traditional Ukrainian feasts and family celebrations, and includes recipes for appetizers, soups, salads, breads, meat, poultry, fish, vegetables, and desserts.
Keywords: Cooking, Ukrainian.; Holiday cooking.; Ukraine -- Social life and customs.; Cuisine des jours de fête.; COOKING -- General.; SOCIAL SCIENCE -- Ethnic Studies -- General.; Cooking, Ukrainian; Holiday cooking; Manners and customs; Ukraine; Kookkunst.; Cookbook; cookbooks.; Cookbooks; Cookbooks.; Livres de cuisine.